Download presentation

Presentation is loading. Please wait.

Published byMichael Nute Modified over 2 years ago

1
Hess’ Law Extra Practice Problems

2
1.From the following enthalpy changes, S (s) + 3 / 2 O 2 (g) SO 3 (g) H = kJ 2 SO 2 (g) + O 2 (g) 2 SO 3 (g) H = kJ calculate the value of H for the reaction S (s) + O 2 (g) SO 2 (g) flip same S (s) + 3 / 2 O 2 (g) SO 3 (g) H = kJ 2 SO 3 (g) 2 S (s) 2 3 2 SO 2 (g) + O 2 (g) H = kJ 2 2( ) 2 +2 O 2 (g) 2 SO 2 (g) H = kJ 2 = kJ

3
2.From the following enthalpy changes, H 2 (g) + ½ O 2 (g) H 2 O (ℓ) H = kJ N 2 O 5 (g) + H 2 O (ℓ) 2 HNO 3 (aq) H = 76.6 kJ ½ N 2 (g) + 3 / 2 O 2 (g) + ½ H 2 (g) HNO 3 (aq) H = kJ calculate the value of H for the reaction 2 N 2 (g) + 5 O 2 (g) 2 N 2 O 5 (g) flip same ½ N 2 (g)+ 3 / 2 O 2 (g)+ ½ H 2 (g) HNO 3 (aq) H = kJ 2 HNO 3 (aq) N 2 O 5 (g) + H 2 O (ℓ) H = kJ H = kJ H 2 (g) + ½ O 2 (g)H 2 O (ℓ) flip ( ) 3 N 2 (g) O 2 (g) N 2 O 5 (g) H = 14.2 kJ ( ) = 28.4 kJ

4
3.From the following enthalpy changes, C (s) + O 2 (g) CO 2 (g) H = kJ H 2 (g) + ½ O 2 (g) H 2 O (l) H = kJ C 5 H 12 (g) + 8 O 2 (g) 5 CO 2 (g) + 6 H 2 O (l) H = 3536 kJ calculate the value of H for the reaction 5 C (s) + 6 H 2 (g) C 5 H 12 (g). same flip C (s) + O 2 (g) CO 2 (g) H = kJ same H 2 (g) + ½ O 2 (g) H 2 O (l) H = kJ C 5 H 12 (g) + 8 O 2 (g) H = 5 CO 2 (g) + 6 H 2 O (l)+3536 kJ ( ) ( ) 5 C (s)+6 H 2 (g) C 5 H 12 (g) H = kJ

5
4.From the following enthalpy changes, CO (g) + SiO 2 (s) SiO (g) + CO 2 (g) H = kJ 3 SiO 2 (s) + 2 N 2 O (g) + 8 CO (g) 8 CO 2 (g) + Si 3 N 4 (s) H = kJ calculate the value of H for the reaction 5 CO 2 (g) + Si 3 N 4 (s) 3 SiO (g) + 2 N 2 O (g) + 5 CO (g) flip same CO (g) + SiO 2 (s) SiO (g) + CO 2 (g) H = kJ 8 CO 2 (g) + Si 3 N 4 (s) 5 CO 2 (g) 33 3 SiO 2 (s) + 2 N 2 O (g) + 8 CO (g) H = kJ 3 3( ) +Si 3 N 4 (s) 3 SiO (g) H = kJ N 2 O (g) 5 CO (g) + +

6
5. From the following enthalpy changes, H 2 (g) + ½ O 2 (g) H 2 O (l) H = kJ SO 3 (g) + H 2 O (l) H 2 SO 4 (l) H = kJ H 2 SO 4 (l) + Ca (s) CaSO 4 (s) + H 2 (g) H = kJ Ca (s) + ½ O 2 (g) CaO (s) H = kJ calculate the value of H for the reaction CaO (s) + SO 3 (g) CaSO 4 (s). same flip same SO 3 (g) + H 2 O (l) H 2 SO 4 (l) H = kJ H 2 (g) + ½ O 2 (g) H 2 O (l) H = kJ H 2 SO 4 (l) + Ca (s) CaSO 4 (s) + H 2 (g) H = kJ CaO (s) H = Ca (s) + ½ O 2 (g) kJ same SO 3 (g)+CaO (s) CaSO 4 (s) H = kJ

Similar presentations

© 2017 SlidePlayer.com Inc.

All rights reserved.

Ads by Google